Selectivity enhancement in the catalytic hydrogenation of propionitrile using ionic liquid multiphase reaction systems - Obert, Katharina; Roth, Daniel; Ehrig, Martin; Schönweiz, Andreas; Assenbaum, Daniel; Lange, Harald; Wasserscheid, Peter (Applied Catalysis A-General, 2009)
A new ionic liquid based, multiphase reaction system was investigated for the catalytic hydrogenation of propionitrile. The reaction system under investigation consisted of a solid heterogeneous Ru-catalyst (Ru on carbon), two liquid phases and the hydrogen gas-phase. By using two liquid phases in the reactor – of which one was an ionic liquid – it was possible to improve significantly the selectivity for the formation of propylamine by suppressing consecutive reactions to dipropylamine and tripropylamine. This enhanced selectivity resulted either from the protonation of the primary formed amine (in case of the Brønsted acidic ionic liquids dimethylcyclohexylammonium hydrogensulfate and 1-butylimidazolium hydrogensulfate) or from the extraction of the primary amine into the organic phase (in case of a 1-ethyl-3-methylimidazolium ethylsulfate/1,2,4-trichlorobenzene biphasic system).